Internet Memes as Reading Controls in a Geometric Road Design Course - García-Ramírez, Yasmany (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Technological development and access are currently leading to changes in the habits of population such as access to information. Short videos and images are used in newspapers, social networks, and university education. Images or internet-meme has been used in several areas of knowledge to improve the students learning, but not in the road design, which content is hand-delivered traditionally. Therefore, this study aims to show an academic activity using internet memes to analyze a weekly topic before synchronous virtual classes. To do this, four groups of students from the Geometric Road Design course participated. They were asked to review the weekly academic content before the class and prepare an internet meme, and their classmates graded those images. As a result, the memes can be used as reading controls before attending the virtual session. They could also be employed before a face-to-face class. The students agreed with the use of memes but were less enthusiastic about the peer review. Despite this trend, the memes produced in combination with peer review increases the possibility of a student to understand the subject. The groups gave an average score to the course of 8.86/10. They were aware of their self-learning with an average rating of 7.74/10. This article describes the experience of students using internet-memes and evaluates the pros and cons.